Trends and Challenges in Agricultural Commodity Prices: A Bibliometric Review of Market Fluctuations and Policy Interventions - Judijanto, Loso; Kartika Lestari, Putu Fajar; Prayana, Yana (West Science Interdisciplinary Studies, 2025)
Agricultural commodity prices are subject to significant volatility, driven by a complex interplay of economic, environmental, and geopolitical factors. This study employs a bibliometric approach to systematically analyze global research trends related to agricultural price fluctuations and policy responses. Drawing on 20 years of data from the Scopus database, we examine the evolution of key themes, influential authors, institutional collaborations, and geographical contributions within the academic literature. Using VOSviewer, keyword co-occurrence, temporal mapping, and authorship networks were visualized to reveal the intellectual structure of the field. The analysis identifies three dominant thematic clusters: sustainability and land-use dynamics, market and crop-specific price behavior, and policy interventions in agricultural trade. Results show a growing shift in recent years toward interdisciplinary research encompassing biofuels, supply chain resilience, energy linkages, and technological innovations. The United States, United Kingdom, China, and Brazil emerge as major contributors to the literature, with strong collaborative ties across regions. Despite the field’s diversity and maturity, the study highlights gaps in evaluating long-term policy effectiveness and the underrepresentation of low-income, agriculture-dependent nations. This review offers valuable insights to inform future research directions and guide more inclusive, data-driven policy frameworks for managing agricultural commodity price volatility.